CUISINE AS A MARKER OF CULTURAL IDENTITY. A HERMENEUTIC LOOK AT “INDIAN CUISINE”, A SHORT STORY BY TRINIDADIAN-CANADIAN WRITER RAMABAI ESPINET - Mario Vicente Ricalo Borrero (European Scientific Journal, ESJ, 2014)
When it comes to cultural identity, cuisine is generally overlooked or relegated. Emphasis is rather made on history, religion or language (the so-called deep structure of a culture). Notwithstanding, one´s vernacular cuisine outlives one´s vernacular language in generations of immigrants. No matter how much it changes as compared to the original food of their homeland, immigrants and their descendants “keep cooking and eating some version of the family´s ‘mother cuisine’ ”. Immigrants’ cultural identity is embodied in what has been called “ethnic food”, which is in turn caused by several factors. The author of this paper examines cuisine as a marker of cultural identity and, for that purpose, he gives a hermeneutic look at the short story “Indian Cuisine”, by adhering to Daniel Chandler´s typology of codes.